Environmental pollution and management - Mphan, I. (New Delhi : Ashi publishing house, 1989)
Pollution is a major threat to our environment. Researchers across the globe are working extensively to devise techniques and methods to mitigate its negative impact. The topics included in this book, such as sustainable use of environmental resources, waste management, effects of pollutants in air, water and soil, environmental quality management, etc., are of utmost significance and bound to provide incredible insights to readers. The extensive content of this text provides the readers with a thorough understanding of the subject. In this book, using case studies and examples, constant effort has been made to aid the sound understanding of the rapid progress made in this significant field.
Includes references and index.
Keywords: Environmental management; Environmental protection; Environmental protection